AgentAPI: an API for the development of managed agents - Lopes, Rui Pedro (2009)
Managed agents, namely SNMP agents, costs too much to develop, test and maintain. Although assuming simplicity since its origins, the SNMP model has several intrinsic aspects that make the development of management applications a complex task. However, there are tools available which intend to simplify this process by generating automatic code based on the management information definition. Unfortunately, these tools are usually complicated to use and require a strong background of programming experience and network management knowledge. This paper describes an API for managed agent development which also provides multiprotocol capabilities. Without changing the code, the resulting agent can be managed by SNMP, web browsers, wap browsers, CORBA or any other access method either simultaneously or individually.